KEBIJAKAN PEMBANGUNAN KAWASAN INDUSTRI YANG BERWAWASAN LINGKUNGAN (ECO-INDUSTRIAL PARK) - Yunita Ismail (President University, 2016)
The construction industry by concentrating the industry in one place, which is called as an industrial area, is intended to suppress the spread of the environmental impact of the industry. Another goal is that the existence of the industry in the same place will double impact on society. Bu tthese objectives must be followed by the fulfillment of strict criteria. Such criteria starting from the allotment of land for the establishment of industrial zones, to the obligations of waste management or environmental impact. Industrial estate development policy must pay attention to the environmental aspects thus awakened environmentally sound industrial area.